Lymphatic mapping of the upper limb with lymphedema before lymphatic supermicrosurgery by mirroring of the healthy limb. Issue 8 (27th September 2017) - Gentileschi, Stefano; Servillo, Maria; Albanese, Roberta; De Bonis, Francesca; Tartaglione, Girolamo; Salgarello, Marzia
Abstract : Introduction: Supermicrosurgical lymphatic‐venous anastomosis (LVA) can improve limbs lymphedema. We describe a technique that we employ for preoperative lymphatic mapping of the upper limb (UL), when indocyanine green (ICG) lymphography shows only dermal backflow (DB) and no lymphatic vessel is detectable. Patients and methods: Sixteen patients undergoing LVA for unilateral UL lymphedema, showing "stardust" or "diffuse" DB pattern, were included. Demographic, clinical data, and limbs measurements were recorded. LymQoL arm questionnaire was administered. Mean age of patients was 58.8 ± 13.1 years. Fifteen were females and 1 male. Lymphatic anatomy of the healthy limb was investigated by ICG lymphography and reported on the affected limb by a four steps technique: marking the main lymphatic pathway on the healthy limb, measuring of the distances at seven levels between the pathway and a line joining fixed landmarks, reporting these measurements on the affected limb with a correction proportional to the degree of swelling, marking skin incisions at the intersection of this pathway with venules, individuated by near infrared light system. Results were analyzed by postoperative questionnaire and changes of limb measurements. Results: For every limb, we could find 3 ± 0.73 incision sites each containing at least one lymphatic vessel suitable for anastomosis. In every patient, we could perform 3.38 ± 0.62 anastomoses. Mean follow‐up was 12.13 ± 2.73 months. After surgery, mean preoperative QoL score increased from 5.5 to 7.9 ( P < .001), and mean difference between the mean circumferences of the affected and healthy limbs decreased from 4.3 ± 1.3 to 2.5 ± 1.3 cm, showing improvement of swelling after surgery ( P < .01). Conclusion: This technique allowed to preoperatively map UL lymphatics even if diffuse DB was present.